The Effectiveness of Implementing the Restorative Justice Model in Handling Domestic Violence (KDRT) Cases in the Papua Regional Police - Abdul Hatta; Yohanis Sudiman Bakti; Roida Hutabalian (PT. AVID MEDIA INDONESIA, 2026)
This study aims to analyze the effectiveness of the implementation of the restorative justice model in handling Domestic Violence (DV) cases in the Papua Regional Police and identify factors that influence its effectiveness. Domestic violence is a form of crime that not only causes physical harm, but also profound psychological and social impacts on victims and all family members. In its development, the restorative justice approach has become an alternative case resolution that prioritizes restoring relationships between victims, perpetrators, and the community through deliberation and agreements oriented towards restoring the original state. This study uses an empirical legal research method with a qualitative approach, where data is obtained through in-depth interviews, field observations, and documentation studies with police officers, victims, perpetrators, community leaders, and related parties within the Papua Regional Police. The results of the study indicate that the implementation of the restorative justice model has been quite effective, especially in cases that meet the requirements for a peaceful resolution. This approach is able to provide faster resolutions, reduce the burden of the criminal justice process, and encourage the creation of peace and restoration of social relations between the parties. The effectiveness of its implementation is influenced by factors of law enforcement officers, factors of victims and perpetrators, factors of culture and social conditions of the community, as well as factors of availability of supporting facilities and infrastructure.